Aquisição e processamento do eletrocardiograma para auxílio ao diagnóstico de arritmias cardíacas - Sousa, Letícia Ainoan Nunes de (Universidade Federal Rural do Semi-Árido, 2018)
According to data from Brazilian Society of Cardiac Arrhythmias, more than 200 million Brazilians have some type of cardiac arrhythmia, a disease responsible for more than 300 thousand deaths per year in the country. However, it is possible to reverse this number, since 90% of these cases could be avoided with prior diagnosis.. Therefore, this work proposes to perform the acquisition, analysis and processing of electrocardiogram of cardiac biopotential, in order to assist in the diagnosis of cardiac arrhythmias. A system of acquisition of the eletrocardiograma was developed, as well as, carried through the processing of its data from an algorithm implemented in software MATLAB, to determine the cardiac frequency and with this to assist in the diagnosis of cardiac arrhythmias. The system was validated with the acquisition of the eletrocardiograma of five volunteers, as well as, its processing, with the determination of the cardiac frequency, in accordance with the waited one
Monografia
Keywords: Eletrocardiograma; Arritmia cardíaca; Aquisição do biopotencial; Processamento do biopontencial; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA